Implementasi Algoritma Boyer-Moore pada Aplikasi Kamus Kedokteran Berbasis Android - Kencana Wulan Argakusumah; Seng Hansun (Ultimatics : Jurnal Teknik Informatika, 2014)
Dictionary is a reference book that contains words and phrases that are usually arranged alphabetically and followed by description of the meaning, usage, or translation. Dictionary has several kinds, one of which is a dictionary of terms. Medical Dictionary is a dictionary of terms that contain medical terms. Medical dictionary identical with the thick book that complicated and slow in its use. To overcome this we need a medical dictionary application. Medical dictionary applications require a search process to support the performance of the application. Search process is needed to shorten the time in the search itself. Searching is done using the Boyer - Moore algorithm is a string search algorithm that has the fastest searching time, because the strings match moves from right to left, so can shorten the time and simplify the use of medical dictionary application. This research was made based on Android using Java programming language with SQLite databases. After testing, 100% of 45 respondents stated that the application of this medical dictionary has the accuracy of the resulting word in the search process. Index Terms - medical dictionary application, search string, Boyer-Moore algorithm, Java, SQLite